Some Fixed Point Theorems in Complex Valued b-Metric Spaces. (26th January 2015) - Dubey, A. K.; Shukla, Rita; Dubey, R. P.
Abstract : Recently, Azam et al. introduced the notion of complex valued metric spaces and proved fixed point theorems under the contraction condition. Rao et al. introduced the notion of complex valued b-metric spaces. In this paper, we obtain some fixed point results for the mapping satisfying rational expressions in complex valued b-metric spaces. Also, an example is given to illustrate our obtained result.